Fabrication and characterization of light-sensing device based on transparent ZnO thin film prepared by sol-gel - Soylu, M.; Yakuphanoğlu, Fahrettin (Elsevier Gmbh, 2016)
In this work, sol-gel method is used for obtaining the ZnO films. The device is constructed from aluminum and n-type ZnO thin film deposited on top of an n type-silicon substrate. Although the structure is formed from the same type semiconductor materials, it exhibits a rectifying behavior. While the similar studies are found in the open literature for ZnO and Si single crystal, we focus on photoelectrical characteristics of n-ZnO/n-Si isotype device. It is seen that reverse bias I-V characteristics are sensitive to light. It has been seen that the interface capacitance for the device is increased with the illumination effect. It is noted that the illumination dependence of interface capacitance can be used to determine the photo-induced interface states. (C) 2016 Elsevier GmbH. All rights reserved.
Keywords: Optical materials; Sol-gel growth; X-ray diffraction; Electrical properties